Pengaruh Kemampuan Membaca Al-Qur’an Terhadap Prestasi Belajar Pendidikan Agama Islam dan Budi Pekerti di SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo - Ilma, Liulil Ussisa; Zuhri, Badrudin; Imama, Nur (PT. AHLAL PUBLISHER NUSANTARA, 2025)
The problems examined in this study are: How is the Qur’an reading ability of students at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo? How is the learning achievement in Islamic Religious Education and Character Education at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo? How does the ability to read the Qur’an influence the learning achievement of Qur’an and Hadith studies at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo? This research was conducted at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo using a quantitative method. The data collection instruments used in this study include questionnaires as the primary data collection tool, and interviews, observations, and documentation as secondary data collection instruments. Data analysis employed percentage techniques for descriptive data and the product moment analysis technique for quantitative data. The results of the study show that the Qur’an reading ability of students at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo, based on the questionnaire distributed to 145 students as respondents, is considered effective. The findings indicate that 68% fall into the good category because they are above the average score of 33.21, while 32% fall into the poor category because they are below the average score of 33.21. Meanwhile, the results regarding the learning achievement of Islamic Religious Education and Character Education based on daily test scores show satisfactory performance, with 53% in the good category (above the average score of 85) and 47% in the poor category (below the average score of 85). Furthermore, the results regarding the influence of Qur’an reading ability (variable X) on learning achievement in Islamic Religious Education and Character Education (variable Y) indicate a significant effect. This is evidenced by the calculated r-value rhitung of 0.414, whereas the r-table value at a 5% significance level is 0.159 and at 1% is 0.208. Therefore, rtabel is greater than rhitung rtabel. Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. Therefore, it can be concluded that the ability to read the Qur’an has an influence on the learning achievement of Islamic Religious Education and Character Education at SMK Yayasan Pendidikan Ma’arif 8 Sidoarjo.